Pengembangan Manajemen Kurikulum Integratif untuk Madrasah Diniyah: Menghubungkan Ilmu Tahajud, Tafsir Al-quran dan Manajemen Pembelajaran yang Partisipatif - Agung Mandiro Cahyono; Anwar Mukti; M. Luqman Hakim; Moh. Bahrudin; Ahmad Nur Fathoni; Ana Asyifa Azzahro (Sciences du Nord Community Service, 2025)
This community service program focuses on developing an integrative curriculum management model for Madrasah Diniyah that connects Ilmu Tahajud, Qur’anic exegesis (Tafsir al-Qur’an), and participatory learning management. The initiative responds to the need to strengthen the quality of nonformal Islamic education by integrating spiritual practice, textual understanding, and collaborative pedagogical approaches within a unified framework. Using a Participatory Action Research (PAR) approach, the program engaged teachers, local religious leaders, and community members in co-designing curriculum components that reflect both classical Islamic knowledge and contemporary learning needs. Activities included needs assessment workshops, curriculum mapping sessions, teacher training on participatory methods, and pilot implementation of integrative learning modules. Results show that embedding Ilmu Tahajud enhances learners’ spiritual discipline and motivation, while structured Tafsir al-Qur’an sessions improve interpretive skills and contextual engagement with the Qur’anic text. When paired with participatory learning management—such as dialogic teaching, co-planning, and reflective evaluation—the integrated model fosters higher student engagement, stronger teacher collaboration, and greater community ownership of the educational process. This program demonstrates that integrative curriculum management can serve as a viable strategy for empowering Madrasah Diniyah to elevate learning quality while maintaining their spiritual and cultural identity.